2006
DOI: 10.1038/nbt1236
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of DNA microarray results with quantitative gene expression platforms

Abstract: We have evaluated the performance characteristics of three quantitative gene expression technologies and correlated their expression measurements to those of five commercial microarray platforms, based on the MicroArray Quality Control (MAQC) data set. The limit of detection, assay range, precision, accuracy and fold-change correlations were assessed for 997 TaqMan Gene Expression Assays, 205 Standardized RT (Sta)RT-PCR assays and 244 QuantiGene assays. TaqMan is a registered trademark of Roche Molecular Syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
460
1
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 553 publications
(495 citation statements)
references
References 23 publications
29
460
1
5
Order By: Relevance
“…It was demonstrated that data from the two different technologies, microarray and real-time rtPCR, yield comparable results [Canales et al, 2006;Morey et al, 2006]. In the present study, regulation of all tested up-regulated genes was confirmed.…”
Section: Discussionsupporting
confidence: 69%
“…It was demonstrated that data from the two different technologies, microarray and real-time rtPCR, yield comparable results [Canales et al, 2006;Morey et al, 2006]. In the present study, regulation of all tested up-regulated genes was confirmed.…”
Section: Discussionsupporting
confidence: 69%
“…Due to the mRNA length, it is currently hardly possible to work with a fully synthetic mRNA standard as presented here for miRNAs. Therefore, although the different available microarray platforms for mRNA expression profiling have been extensively evaluated (Canales et al 2006), there is still no gold standard for quantifying mRNA transcript concentrations by microarrays. The approaches developed so far encompass mathematical modeling (Hekstra et al 2003;Frigessi et al 2005), calibrated reference samples (Dudley et al 2002), exogenous RNA controls (Carter et al 2005b), and combinations of mathematical modeling and spike measurements (Zhao et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, slight differences in relative quantitation levels are not unexpected and studies have been conducted to assess differences in relative gene expression data obtained using different technology platforms. 5,31,32 Macroarray analysis relies on hybridization of labeled cDNA to probe regions on a nylon filter, whereas real-time PCR and GeXP assays involve PCR amplification procedures using primer assays. The preparation of labeled cDNA required for macroarray analysis thus is significantly different from production of reverse-transcribed cDNA for use as a template for PCR amplification.…”
Section: Org)mentioning
confidence: 99%